Atomistic Modeling of Fluorine Implantation and Diffusion in III-Nitride Semiconductors - Li Yuan; Wang, Maojun; Chen, Kevin J. (IEEE INTERNATIONAL ELECTRON DEVICES MEETING 2008, TECHNICAL DIGEST, 2008)
A hybrid molecular dynamics (MD)/kinetic Monte Carlo (KMC) model is developed for atomistic modeling of fluorine ion implantation and diffusion in AlGaN/GaN heterostructures. The MD simulation reveals the F distribution profiles and the corresponding defect profiles, and most importantly, the potential energies of fluorine ions in the III-nitride material system. Using the results from the MD simulation, the diffusion process is simulated with KMC method, and the modeling results are validated by the secondary-ion-mass-spectrum (SIMS) measurement. The surface effect on the fluorine's stability and its improvement by passivation are also successfully modeled.